2019
DOI: 10.1128/aac.01876-18
|View full text |Cite
|
Sign up to set email alerts
|

MSH2 Gene Point Mutations Are Not Antifungal Resistance Markers in Candida glabrata

Abstract: The high rates of antifungal resistance inCandida glabratamay be facilitated by the presence of alterations in theMSH2gene. We aimed to study the sequence of theMSH2gene in 124 invasiveC. glabrataisolates causing incident episodes of candidemia (n= 81), subsequent candidemia episodes (n= 9), endocarditis (n= 2), andin vitro-generated echinocandin-resistant isolates (n= 32) and assessed its relationship with genotypes, acquisition of antifungal resistancein vivoandin vitro, and patient prognosis. TheMSH2gene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…We studied 10 pairs of molecularly identified C. glabrata isolates (26) involving parental echinocandin-susceptible isolates causing candidemia and isogenic echinocandin-resistant ones either generated in vitro (n ϭ 8) (27,28) or recovered from the heart valves of patients with concomitant endocarditis (n ϭ 2). Microsatellite markers showed that the parental and isogenic isolates had the same genotype (29). The characteristics of the isolates are shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…We studied 10 pairs of molecularly identified C. glabrata isolates (26) involving parental echinocandin-susceptible isolates causing candidemia and isogenic echinocandin-resistant ones either generated in vitro (n ϭ 8) (27,28) or recovered from the heart valves of patients with concomitant endocarditis (n ϭ 2). Microsatellite markers showed that the parental and isogenic isolates had the same genotype (29). The characteristics of the isolates are shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…The acquisition of such mutations in genes associated with resistance may occur in the presence of specific mutations/absence of DNA repair mechanisms, such as mismatch repair (MSH2), resulting in increased antifungal tolerance and virulence [32,33]. Of note, the link between MSH2, in vitro tolerance, and clinical tolerance is uncertain [34,35].…”
Section: Antifungal Tolerance Molecular Mechanisms and Its Implicatiomentioning
confidence: 99%
“…Recently, it was proposed that the presence of mutation(s) in a gene of DNA repair pathway, MSH2, increases the propensity of clinical C. glabrata isolates to acquire in vitro resistance to antifungal drug(s) [60]. This notion has been evaluated in French [136], Chinese [124], Spanish [35], and Indian [137] clinical isolates of C. glabrata, and it appears that the presence of a mutation in MSH2 is associated with the genotype but not with the acquisition of antifungal resistance. Although, these clinical studies reported little or no resistance, which makes biological associations seems suspicious.…”
Section: Candida Glabratamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in Cryptococcus , naturally occurring mutations in MSH2 have been shown to contribute to microevolution and population diversity (59, 60). Yet, recent clinical studies have not found an association between specific MSH2 alleles and drug resistance (2729, 61, 62), raising the question of whether clinical isolates carrying these alleles are true mutators. To answer this question, it is necessary to measure and directly compare mutation rates between clinical isolates of C.…”
Section: Introductionmentioning
confidence: 99%